THE RELATIONSHIP BETWEEN SPIRITUALITY AND ADOLESCENT RESILIENCE AFTER THE MOUNT SEMERU ERUPTION DISASTER IN PRONOJIWO VILLAGE, LUMAJANG REGENCY - Mufarika (EZRA SCIENCE BULLETIN, 2024)
The Semeru Mount eruption disaster causes feelings of anxiety, anxiety, and grief. From the result of a preliminary study conducted by researchers at he ANNUR Foundation, Pronojiwo Village, Lumajang Regency,it wa found that some adolescents experienced low and moderate resilience . The purpose of this study is to determine the relationship between spirituality and the resilience of adolescents after the eruption of Mount Semeru. The research design used analytic with a cross sectional approach. The independent variable was spiritual. The dependent variable was adolescent resilience. The population is 66 adolescents aged 14-16 years at the Annur Sumberurip Foundation school, Pronojiwo Village, Lumajang Regency, with a sample taken is 56. The sampling technique used probability sampling with a proportional random sampling technique. Data collection techniques using a questionnaire. The statistical test used the Spearman rank test with (a = 0.05). This research has been carried out ethical clearance test by KEPK STIKes Ngudia Husada Madura team. The results of the statistical Spearman rank test obtained a value of p = 0.000 <α (0.05). Thus it be concluded that there was a relationship between spirituality and resilience of adolescents post the eruption of Mount Semeru at the ANNUR Foundation, Pronojiwo Village, Lumajang Regency. With and r value = 0.951 means that spirituality and resilience are strongly related. It is recommended that this research be used as a data source for further research related to the relationship between spirituality and resilience in adolescents after a volcanic eruption by adding other factors that can affect spirituality in adolescents. Health workers are also advised to make it a reference in providing nursing care to adolescents who experience resilience. For respondents to do self-development by increasing spirituality by attending more frequently at taklim majlis events as a means of increasing their sincerity in exploring spirituality